Evolution of Exchange Rate Behavior in the ASEAN-5 Countries - Klyuev, Vladimir (IMF Working Papers; Working Paper ;, 2016)
This paper examines exchange rate behavior in the ASEAN-5 countries (Indonesia, Malaysia, the Philippines, Singapore, and Thailand). It finds that for the last 10 years there is no evidence that their central banks target particular exchange rate levels against any currency or basket. Thus, contrary to some assertions, they do not belong to a U.S. dollar club, a Japanese yen club, a Chinese renminbi club, or an ASEAN club. At the same time, they clearly try to smooth short-term volatility, particularly vis-a-vis the U.S. dollar. The degree of smoothing declined noticeably after the Asian Financial Crisis and less obviously after the Global Financial Crisis, with heterogeneity across countries. Short-term smoothing without level targeting does not interfere with monetary policies aimed at price stability.